The Political Premises of Contemporary Urban Concepts: The Global City, the Sustainable City, the Resilient City, the Creative City, and the Smart City. (15th March 2018) - Hatuka, Tali; Rosen-Zvi, Issachar; Birnhack, Michael; Toch, Eran; Zur, Hadas
Abstract: Numerous studies have focused on the global city, the sustainable city, the resilient city, the creative city, and the smart city, analyzing their politics, ideologies, and social implications. However, the literature lacks synthetic analysis that addresses these concepts by juxtaposing them and exploring their similarities and differences. This paper provides synthetic analysis, followed by a discussion of the concepts' competing and complementary logics of governance and citizenship. The concluding section addresses the importance of taking into account these diverse concepts as political ideas and discusses how these concepts become a prescriptive mix promoted by public officials and private developers.